2023
DOI: 10.3389/frsc.2023.1192588
|View full text |Cite
|
Sign up to set email alerts
|

Urban bee functional groups response to landscape context in the Southeastern US

Abstract: We investigated the influence of landscape cover on urban bee community functional groups. We observed a diversity of functional groups across primarily forested and primarily urban sites, however particular species were favored by forest/urban spaces. Results point to the importance of further investigating the nuance of land use impacts on pollinator communities, and in particular demonstrates the merit of investigating landscape heterogeneity. Conservation of forest remnants in urban environments can positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Estimates from northeastern US suggest that roughly 32% of bee species are forest associated, and an additional 31% of bees are habitat generalists which may use forests in some capacity (Smith et al, 2021). While we do not have estimates of forest-associated species within the southeastern US, recent studies within the same geographical area (Athens-Clarke, Co., Georgia, USA) suggest that forest cover impacts bee diversity at small and large spatial scales (Janvier et al, 2022;Traylor et al, 2022;Braman et al, 2023). We were interested in further determining species and functional diversity at the urban-forest interface.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Estimates from northeastern US suggest that roughly 32% of bee species are forest associated, and an additional 31% of bees are habitat generalists which may use forests in some capacity (Smith et al, 2021). While we do not have estimates of forest-associated species within the southeastern US, recent studies within the same geographical area (Athens-Clarke, Co., Georgia, USA) suggest that forest cover impacts bee diversity at small and large spatial scales (Janvier et al, 2022;Traylor et al, 2022;Braman et al, 2023). We were interested in further determining species and functional diversity at the urban-forest interface.…”
Section: Introductionmentioning
confidence: 81%
“…We did not find a significant relationship with bee community composition and size or seasonality. Several studies have found no difference in body size between forest types or with development (Fortuin and Gandhi, 2021;Braman et al, 2023). In a 2020 metaanalysis of functional traits in urban areas, body size again offered mix results where 8 studies found a positive relationship while others had none (Buchholz and Egerer, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations